You can see almost immediately that the second equation, 3x + y = -2, can be solved for y: y = -3x - 2. (Answer A). This -3x - 2 can in turn be subbed for y in the first equation, 4x + 3y = 4. Doing so, we get 4x + 3(-3x - 2) = 4.
Carrying out the indicated opeations: 4x - 9x - 6 = 4, or -5x = 10. Thus,
x = -2. Find y using y = -3x - 2 (from above): y = -3(-2) - 2 = 4.
Thus, the solution is (-2,4). We were not asked to solve this system of equations, but doing so illustrates the helpfulness of elimination of variables in solving simultaneous equations.